PEMAHAMAN KONSEPTUAL DAN KESIAPAN GURU SEKOLAH DASAR TERHADAP PENERAPAN DEEP LEARNING DI INDONESIA - Allolinggi, Lutma Ranta; Al Arsyadhi, Nurul Laily; Akbar, Ady (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study adopts a descriptive quantitative approach to examine how elementary school teachers understand and prepare for the implementation of Deep Learning-based instruction. A total of 160 teachers from South Sulawesi Province participated as respondents, selected through purposive sampling that considered their teaching experience and involvement in Deep Learning training. Data were gathered using a validated Likert-scale questionnaire covering five central dimensions, namely conceptual understanding of Deep Learning, pedagogical readiness, technological readiness, motivation for professional growth, and perceptions of institutional challenges and support. The results indicate that teachers’ readiness is uneven across these dimensions. The dimension of technological readiness achieved the highest mean score, categorized as high, particularly among younger teachers who actively use digital tools and artificial intelligence applications to enhance collaboration and provide feedback in the learning process. Conversely, the lowest scores were observed in conceptual understanding and pedagogical readiness. Many teachers still perceive Deep Learning as synonymous with project-based learning and have yet to internalize its philosophical essence, which emphasizes meaningful engagement, reflective thinking, and joyful learning experiences. Teachers’ motivation to develop their professional competence was found to be at a moderate level, with a tendency to depend more on institutional facilitation than on intrinsic drive. These findings highlight that the successful implementation of Deep Learning depends not only on teachers’ technological proficiency but also on their conceptual depth and pedagogical preparedness. Therefore, capacity building for teachers should be designed through an integrative model of professional development that brings together digital literacy, philosophical awareness, and pedagogical reflection within a supportive institutional framework. Such an approach is essential to transform Deep Learning from a theoretical policy initiative into a practical educational reality that nurtures critical, creative, and humanistic learners in the era of artificial intelligence